Pengaruh Penerapan Environmental, Social, Dan Governance Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023) - Rojaba, Niswah Itsna; Nurhajati, Nurhajati; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the effect of Environmental, Social, and Governance on financial performance with company size as a moderating variable (Empirical study of banking companies listed on the Indonesia Stock Exchange. The sample in this study used Purposive sampling and obtained 16 companies so as to obtain 80 research data research data. Data collection techniques in this study using documentation techniques. The data analysis techniques uses PLS (Partial Least Square) analysis using SmartPLS 3.0 software. The result this study prove that environmental has an effect on financial performance. Social hasn’t effect on financial performance, and governance hasn’t effect on financial performance. The result of moderation analysis of company size moderate the effect of environmental on financial performance. While company size cannot moderate the influence of social and governance on financial performance. The implication is that banking companies need to increase awareness of the importance of implementing ESG (Environmental, Social, and Governance) aspects in their operational activities and sustainability reporting, this will increase the trust of investors, stakeholder, the general public and increase the company’s performance. Keywords: Financial Performance, Environmental, Social, Governance, Company Size